An Analysis of Word-Formation Process Used in Students’ Writing at Eighth Grade of Smp Muhammadiyah Mandau - Putri Sutrisno, Azkiya; Kemala Sari, Mezia Kemala Sari; Syandri, Gusmaizal (Journal of Educational Management and Strategy, 2023)
Language is related to word formation processes because it is the process of creating new words and new uses of the old words and also how new words are being formed. This research was about word formation processes used in students‟ writing at Eighth Grade of SMP Muhammadiyah Mandau. The aims of this thesis were to classify and analyze the word formation process used in students‟ writing and also to find out the kinds of word formation processes the most dominant one. The researcher used descriptive qualitative method, in which the data were words that contain word formation processes used in students‟ writing. The data were analyzed applying the theory of word formation processes by Yule (2010). The researcher took 10 students‟ writing as the data. The result of this research, there were 8 types of word formation processes were found in students‟ writing. They were borrowing, coinage, compounding, acronym, clipping, inflection and derivation. In finding the most dominant type of word formation processes was inflection (34.61%) then followed by compounding (22.07%), derivation (15.38%), borrowing (11.54%), acronym (7.7%), clipping (3.85%) and the last coinage (3.85%). As the conclusion, the process of inflection was the most dominant process that was found in students‟ writing. It was 34.61% of total words. It meant that the students used inflection to show plural or singular and tenses. Abstrak Bahasa berkaitan dengan proses pembentukan kata karena merupakan proses penciptaan kata-kata baru dan penggunaan baru dari kata-kata lama dan juga bagaimana kata-kata baru itu terbentuk. Penelitian ini adalah tentang penggunaan proses pembentukan kata pada Tulisan Siswa Kelas VIII SMP Muhammadiyah Mandau. Tujuan dari penulisan peneltian ini adalah untuk memgklasifikasi and menganalisis jenis-jenis dari proses pembentukan kata, kemudian menemukan proses pembentukan kata yang paling dominan di gunakan pada tulisan siswa. Peneliti menggunakan metode deskriptif kualitatif dan data berasal dari tulisan siswa yang mengandung proses pembentukan kata. Peneliti menganalis sebuah temuan dominant dengan menggunakan formula Yule (2010). Dari analisa penelitian ini, peneliti menemukan 7 proses dari pembentukan kata yang digunakan di dalam tulisan siswa yaitu borrowing, coinage, compounding, acronym, clipping, inflection and derivation. Proses pembentukan kata yang paling dominan adalah inflection (34.61%) kemudian diikuti oleh compounding (22.07%), derivation (15.38%), borrowing (11.54%), acronym (7.7%), clipping (3.85%) dan coinage (3.85%). Sebagai kesimpulan peneliti menemukan penggunaan inflection yang paling dominan pada tulisan siswa. Ini makna nya siswa menggunakan inflection untuk menunjukan bentuk tunggal or jamak dan bentuk waktu.